Resource Management and the Effects of Trade on Vulnerable Places and People : Lessons from Six Case Studies - Larson, Donald F.; Nash, John (2012)
Lessons from six case studies illustrate the complex relationships between international trade, vulnerable ecologies and the poor. The studies, taken from Africa, Asia and Latin America and conducted by local researchers, are set in places where the poor live in close proximity to ecologies that are important to global conservation efforts, and focus on the cascading consequences of trade policy for local livelihoods and environmental services. Collectively, the studies show how under-valued common resources are often poorly protected and consequently subject to shifting economic incentives, including those that arise from trade. The studies provide examples where trade works to accelerate the use of natural resources and to exacerbate unsustainable dependencies by the poor, and other examples where trade has the opposite effect. An important conclusion is that local livelihood and technology choices have important consequences for how environmental resources are used and should be taken into account when designing policies to safeguard fragile ecologies.